RESEARCH OF INTERRELATIONS BETWEEN CHEMICAL COMPOSITION OF WATERS AND BOTTOM SEDIMENTS OF SIBERIAN RIVERS - Oleg G. Savichev (Izvestiya Tomskogo Politekhnicheskogo Universiteta Inziniring Georesursov, 2019)
Relevance. Understanding of the mechanism and quantitative estimation of interaction between river waters and bottom sediments substance is a methodological basis of water restoration planning, ecological monitoring and ores hydrogeochemical searches. The aim of the research is the quantitative description of interrelation between the chemical composition of river waters and bottom sediments. Methods: statistical methods, mathematical modelling of hydrogeochemical processes. Results and conclusions. The author has considered the mathematical model of Fe, Cu, Pb, Zn, As interrelations in waters and bottom sediments of some Siberian rivers (the Omutnaya, Ilbokich, Botkich, Top Nemba, Bottom Nemba, Inganba and Aktru rivers; the Omutnaya river in river system Omutnaya–Kirgizka–Tom–Ob rivers; the Ilbokich, Botkich, Top Nemba, Bottom Nemba, Inganba rivers are tributaries of the Chadobets river, system Chadobets–Angara–Yenisei rivers; the Aktru river in system Aktru–Chuya–Katun–Ob rivers). The algorithm of model parameters definition including the regression analysis and optimization methods is proposed. The relations between a chemical composition of river waters and bottom sediments are not linear and depend on absolute and relative characteristics of water exchange intensity, basin marshiness and рН of river waters. The absolute and relative increment of concentration in river waters is usually less than a corresponding increment of concentration in bottom sediments. At the same time, the observed high concentration of Fe and the raised contents of some microelements can be related not only to the natural geochemical anomalies in bottom sediments or water pollution, but also to certain combinations of environmental conditions, for example, to the minimal difference between maxima possible and actual sorption in bottom sediments.